2012
DOI: 10.1002/app.38448
|View full text |Cite
|
Sign up to set email alerts
|

Impact damage sensing of multiscale composites through epoxy matrix containing carbon nanotubes

Abstract: Carbon nanotubes are used to provide increased electrical conductivity for polymer matrix materials, thus offering a method to monitor the structure's health. This work investigates the effect of impact damage on the electrical properties of multiscale composite samples, prepared with woven fiberglass reinforcement and epoxy resin modified with as-received multi-walled carbon nanotubes (MWCNTs). Moreover, this study addresses potential bias from manufacturing, and investigates the effectiveness of resistance m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…On the other hand, it has been proved that carbon nanotubes (CNTs) can provide electrical conductivity to electrically insulating polymers, 2,3 and they may also provide mechanically reinforcement. Coupling between the electrical conductivity and an external excitation can provide sensing capabilities to CNT composites, which can be used for measuring changes in glucose concentration, 4 impact damage 5 the presence of gases, 6 or liquids. 7 CNT/polymer composites with strain sensing capabilities have recently been also aggressively studied.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been proved that carbon nanotubes (CNTs) can provide electrical conductivity to electrically insulating polymers, 2,3 and they may also provide mechanically reinforcement. Coupling between the electrical conductivity and an external excitation can provide sensing capabilities to CNT composites, which can be used for measuring changes in glucose concentration, 4 impact damage 5 the presence of gases, 6 or liquids. 7 CNT/polymer composites with strain sensing capabilities have recently been also aggressively studied.…”
Section: Introductionmentioning
confidence: 99%
“…The method is used in measurements of semiconductor material resistivity. The 4-point method proved to be more reliable and repeatable than measurement by using two electrodes [7]. 4-point measurement scheme is shown on Figure 1.b.…”
Section: Test Setupmentioning
confidence: 99%
“…Arronche et al [80] performed similar experiments for sensing of damage due to impact loads. The resistance changes that the group reported for their composite panel under impact loads were consistent with the work of Gao et al [79], but they reported significant differences in the values obtained by two-and four-wire methods.…”
Section: Sensing Of Localized Impact Damagementioning
confidence: 99%